(untitled) - Tanous, Peter J. (Hoboken, N.J., 2011)
What investors can do to protect their investments in the next phase of the ongoing global economic collapse. The United States is heading toward an unavoidable financial catastrophe that will paralyze the markets and the overall economy in ways never before seen. Some call this impending economic catastrophe a double-dip recession, others a financial Armageddon.. Regardless of what it's called, it is too late to stop it. Debts, Deficits, and the Demise of the American Economy is a look at how we got here, how the crisis is unfolding, and how it will end with a stock market crash in 2012, if not sooner.. Takes you through the unraveling of the collapse, starting with a wave of sovereign debt defaults in Europe. Predicts a stock market decline of two to three thousand points, a run on banks resulting in a major bank crisis, and rampant inflation. Provides investment strategies, including alternative investments such as timber, farm land, and oil. Offers a detailed proposal to get the United States out of the crisis. Debts, Deficits, and the Demise of the American Economy is a must-read, play-by-play account of the worldwide depression that is likely to unfold in the coming years.
Keywords: Business forecasting,Dự báo kinh doanh; United States,Hoa Kỳ